3D-printed chiral torsion Janus evaporator with enhanced light utilization towards ultrafast and stable solar-water desalination. (15th January 2023) - Jin, Zhipeng; Zhang, Minggang; Mei, Hui; Liu, Hongxia; Pan, Longkai; Yan, Yuekai; Cheng, Laifei; Zhang, Litong
Abstract: Solar evaporation is a sustainable, environmentally friendly and promising solution to the problem of fresh water shortage. However, the widespread application of solar evaporators is limited by their spatial geometry, surface salt deposition and durability. Here, a Janus evaporator with a 3D chiral torsion structure is designed using 3D printing technology. Such a structure increases the number of light reflections to improve light collection. At the same time, the top and bottom layers of the Janus evaporator are endowed with different surface wettability. In particular, the top layer of superhydrophobic SiO2 /CNTs aerogel acts as a photothermal absorber and prevents salt deposition, while the bottom layer of superhydrophilic CNTs aerogel accelerates water replenishment and improves water transfer efficiency. At 1 sun, the 3D Janus evaporator exhibits a high evaporation rate of 2.775 kg m −2 h −1 and a solar-to-vapor conversion efficiency of 90.2%. The 3D Janus evaporator demonstrates a strong desalination capacity in simulated seawater and allows one to obtain fresh water above drinking water standards. Moreover, it can work sustainably in different environments and has good cycle stability. The 3D Janus evaporator, prepared by 3D printing, opens up new prospects and great potential to solve the issues associated with fresh water shortage. Graphical abstract: Image 1 Highlights: A Janus evaporator with a 3D chiral torsion structure is designed using 3D printing technology. The top and bottom layers of the Janus evaporator are endowed with different surface wettability. The 3D Janus evaporator shows a high evaporation rate of 2.775 kg m −2 h −1 under 1 sun. The 3D Janus evaporator demonstrates a strong desalination capacity and allows one to obtain fresh water.